Exploration and Practice of "Three-Dimensional Integration" Training Model for Professional Degree Postgraduates - Yi Zhang, Xiaobo Wang, Jisheng Ma, Fang Xie (Forest Chemicals Review, 1970)
In the current training process of professional degree postgraduates, the three elements of scientific research project, discipline competition and dissertation are not integrated, and the related teaching, research and teaching reform research is mostly limited to the relationship between the two. This paper takes the cultivation of innovation ability and engineering practice ability as the core. Guided by scientific research projects and discipline competitions, it breaks down the barriers to explore the mechanism of how to connect the three elements, studies and constructs a "three-dimensional integration" innovative training model to form an efficient cultivation model for professional degree postgraduates.